Profile of dermatological consultations in Brazil (2018) - Miot, Hélio Amante (2018)
Background: Dermatological diseases are among the primary causes of the demand for basic health care. Studies on the frequency of dermatoses are important for the proper management of health planning. Objectives: To evaluate the nosological and behavioral profiles of dermatological consultations in Brazil. Methods: The Brazilian Society of Dermatology invited all of its members to complete an online form on patients who sought consultations from March 21-26, 2018. The form contained questions about patient demographics, consultation type according to the patient's funding, the municipality of the consultation, diagnosis, treatments and procedures. Diagnostic and therapeutic decisions were compared between subgroups. Results: Data from 9629 visits were recorded. The most frequent causes for consultation were acne (8.0%), photoaging (7.7%), nonmelanoma skin cancer (5.4%), and actinic keratosis (4.7%). The identified diseases had distinct patterns with regard to gender, skin color, geographic region, type of funding for the consultation, and age group. Concerning the medical conducts, photoprotection was indicated in 44% of consultations, surgical diagnostic procedures were performed in 7.3%, surgical therapeutic procedures were conducted in 19.2%, and cosmetic procedures were performed in 7.1%. Study limitations: Nonrandomized survey, with a sample period of one week. Conclusion: This research allowed us to identify the epidemiological profiles of the demands of outpatients for dermatologists in various contexts. The results also highlight the importance of aesthetic demands in privately funded consultations and the significance of diseases such as acne, nonmelanoma skin cancer, leprosy, and psoriasis to public health.